Evidence that transferrin may function exclusively as an iron donor in promoting lymphocyte proliferation. - Brock, J H (1986)
In order to distinguish between a requirement for iron and a possible additional requirement for the iron-binding protein transferrin per se, the ability of mouse lymphocytes to proliferate in response to concanavalin A has been investigated. Cells proliferated well when cultured in medium containing 5% fetal calf serum, but if iron-free mouse or human transferrins were added, proliferation was inhibited by greater than 80%, whereas the same transferrins saturated to 30% with iron enhanced proliferation by 40-70%. In serum-free medium, proliferation was greater in the presence of 30% iron-saturated transferrin than when the protein was saturated only to 10%. Addition of Mn3+ to the latter, to bring the total metal saturation to 30%, gave no improvement in proliferation. Lymphocytes took up iron preferentially when transferrin containing both iron and manganese was present in the culture medium. The degree of proliferation in serum-free medium in the presence of a variant of human transferrin with abnormal iron-binding and receptor-binding properties was almost identical to that when normal human transferrin was used. Finally, when a monoclonal antibody to the mouse transferrin receptor and iron-nitriotriacetate were substituted for iron-transferrin in serum-free medium, proliferation was reduced by greater than 95%. These results strongly suggest that transferrin promotes lymphocyte proliferation solely as a result of its iron-donating properties, and that an additional role such as the provision of a proliferation-inducing membrane signalling event following interaction with the transferrin receptor seems unlikely.